A-290 Ejection Fraction and Trail Making Test-B in Heart Failure Patients. (17th August 2022) - Kung, Jennifer; Connors, Eric J; Hauson, Alexander O; Pollard, Anna A; Sarkissians, Sharis
Abstract: Objective: Ejection fraction (EjF) is used as a clinical indicator of cardiac function and has been associated with reduced executive functioning among heart failure (HF) patients (Hoth, 2008). However, other HF studies have found no association between EjF and neurocognitive measures (Putze, 1998; Wolfe, 2006). This meta-analysis examines the relationship between EjF and executive functioning using the Trail Making Test-B (TMT-B). Data Selection: As part of a larger study, two researchers independently searched eight databases, extracted required data, and calculated effect sizes of HF neuropsychological data. Inclusion criteria for articles were: (a) adults diagnosed with HF, (b) matched control group on demographics (e.g. age), and (c) standardized neuropsychological testing. Exclusion criteria included: (a) comorbidity of HF with other types of major organ failure (i.e., lung or liver failure), (b) data that compared groups with different New York Heart Association (NYHA) classes of HF, or (c) studies not published or translated into English. Eight articles (HF n= 592 and HC n = 268) were analyzed. Data Synthesis: The TMT-B evidenced a statistically significant and medium effect size estimate (g = 0.568, p < 0.001). The heterogeneity of TMT-B was not statistically significant. The meta-regression analysis between EjF and effect size was also not statistically significant (Q=.434, df=1, p=.510). Conclusions: TMT-B detects executive functioning deficits associated with heart failure. A meta-regression did not reveal a significant relationship between EjF and TMT-B. It is likely that other factors moderated this relationship making it difficult to detect an association between these two variables in a diverse sample of studies.